The “Cultural Mission” in Indigenous Non-fiction Book Publishing in Australia 1960–2000. - Davis, Mark (Journal of Australian Studies, 2017)
Non-fiction books by and about Aboriginal and Torres Strait Islanders have arguably played a crucial role in the framing of public discussion of Indigenous issues in Australia since the 1950s. In this article, I track quantitative trends in the publishing of the approximately 769 such books for the Australian retail trade between 1960 and 2000, as part of what I describe as an emerging “cultural mission” among Australian book publishers through the period. The article then discusses two major trends within the data. The first is an overall increase in the number of titles published annually through the period, while the second is a declining interest by mass-market trade publishers in publishing books in the area from the 1980s onwards versus an increased publication rate by smaller independent presses and two large trade publishers with a particular interest in the area, one of which is also independently owned. The article concludes with a discussion of possible reasons for the latter trend in the context of ongoing debates about white Australian colonialism.